Multimodal analysis of verbal behavior and phonological adaptation in children with cerebral palsy: A linguistic case study from Indonesia - Siregar, Elitaria Bestri Agustina; Mulyadi, Mulyadi; Gustianingsih, Gustianingsih; Nasution, Khairina (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates verbal behavior and phonological adaptation in children with Cerebral Palsy (CP) through an intensive case study using a mixed-method approach. Drawing from Skinner’s verbal behavior theory, Chomsky’s generative linguistics, and Blumstein’s model of phonological change, the research analyzes two verbal CP subjects: AK (10 years) and MM (15 years), each observed over 12 sessions. Data collection involved linguistic operant testing (mand, tact, echoic, intraverbal), acoustic analysis via Praat software, and semi-structured interviews with caregivers. Results indicate a significant gap between linguistic competence and verbal performance, largely due to articulatory-motor limitations. Mand operants predominated, reflecting need-driven rather than spontaneous communication. Acoustic analysis revealed systematic phoneme substitution (/p/ → /ʔ/, /s/ → /ʃ/), omission, and vowel elongation, suggesting patterned adaptations. MM exhibited more advanced articulatory control and cognitive abstraction than AK, who remained reliant on external prompts. Methodologically, this research adopts a multimodal framework encompassing verbal, non-verbal, and paralinguistic dimensions to better understand communicative strategies in constrained conditions. Findings underscore the need for adaptive linguistic assessment and responsive communicative environments to support language development in children with CP.